Ceftriaxone improves impairments in synaptic plasticity and cognitive behavior in APP/PS1 mouse model of Alzheimer's disease by inhibiting extrasynaptic NMDAR‐STEP61 signaling - He, Ruo‐Bing; Li, Li; Liu, Li‐Zhe; Ma, Ya‐Jun; Fan, Shu‐Juan; Liu, Li‐Rong; Li, Wen‐Bin; Xian, Xiao‐Hui (Journal of neurochemistry, 2023)
Abnormal activation of the extrasynaptic N‐methyl‐d‐aspartate receptor (NMDAR) contributes to the pathogenesis of Alzheimer's disease (AD). Ceftriaxone (Cef) can improve cognitive impairment by upregulating glutamate transporter‐1 and promoting the glutamate–glutamine cycle in an AD mouse model. This study aimed to investigate the effects of Cef on synaptic plasticity and cognitive‐behavioral impairment and to unravel the associated underlying mechanisms. We used an APPswe/PS1dE9 (APP/PS1) mouse model of AD in this study. Extrasynaptic components from hippocampal tissue homogenates were isolated using density gradient centrifugation. Western blot was performed to evaluate the expressions of extrasynaptic NMDAR and its downstream elements. Intracerebroventricular injections of adeno‐associated virus (AAV)‐striatal enriched tyrosine phosphatase 61 (STEP61) and AAV‐STEP61‐shRNA were used to modulate the expressions of STEP61 and extrasynaptic NMDAR. Long‐term potentiation (LTP) and Morris water maze (MWM) tests were performed to evaluate the synaptic plasticity and cognitive function. The results showed that the expressions of GluN2B and GluN2BTyr1472 in the extrasynaptic fraction were upregulated in AD mice. Cef treatment effectively prevented the upregulation of GluN2B and GluN2BTyr1472 expressions. It also prevented changes in the downstream signals of extrasynaptic NMDAR, including increased expressions of m‐calpain and phosphorylated p38 MAPK in AD mice. Furthermore, STEP61 upregulation enhanced, whereas STEP61 downregulation reduced the Cef‐induced inhibition of the expressions of GluN2B, GluN2BTyr1472, and p38 MAPK in the AD mice. Similarly, STEP61 modulation affected Cef‐induced improvements in induction of LTP and performance in MWM tests. In conclusion, Cef improved synaptic plasticity and cognitive behavioral impairment in APP/PS1 AD mice by inhibiting the overactivation of extrasynaptic NMDAR and STEP61 cleavage due to extrasynaptic NMDAR activation. Glutamate receptor GLT‐1 damage leads to increased perisynaptic glutamate concentration in Alzheimer's disease (AD), which activates extrasynaptic N‐methyl‐d‐aspartate receptor (eNMDAR) and its downstream signaling and causes impairment of synaptic plasticity and cognition. The results showed that ceftriaxone downregulated eNMDAR expression, inhibited eNMDAR‐STEP61 and p38 MAPK signaling, and improved impairments of long‐term potentiation (LTP) and Morris water maze in AD mice. The STEP61‐mediated modulation of eNMDAR confirmed the hypothesis that ceftriaxone exerts anti‐AD effects by improving GLT‐1 impairment and inhibiting the activation of eNMDAR and its downstream signals.